Peran Pemerintah Dalam Pengelolaan Kebersihan Lingkungan Di Kelurahan Koya Kecamatan Tondano Selatan - Yomima Lamera; Apeles Lexi Lonto; Julien Biringan (CV. Kurnia Grup, 2026)
This research was carried out to analyze the government's involvement in environmental cleanliness management, identify obstacles that arise, and examine the efforts made to encourage community participation in Koya Village, South Tondano District. The method used is a qualitative approach, with data collection through in-depth interviews, direct observations in the field, and tracing of supporting documents. The research subjects consisted of village officials, community leaders, and residents of Koya Village. The findings of the study show that the Koya Village Government has shown a fairly active role in maintaining the cleanliness of the environment. This is realized through the implementation of regular community service, the provision of temporary garbage containers, garbage transportation services using a cleaning fleet, as well as socialization activities carried out through RT/RW meetings, the installation of banners, the use of social media, and support from religious leaders and community leaders. However, the implementation of hygiene management still faces a number of obstacles, especially limited facilities such as temporary landfills, garbage transport vehicles, and cleaning equipment. In addition, the low awareness of some people and the lack of cleaning personnel also affect the effectiveness of the programs carried out. In order to increase community involvement, the village government seeks to reactivate routine community service activities, involve schools and youth groups, and provide a simple form of appreciation to the environment that is considered active in maintaining cleanliness. However, the level of community participation is still unstable and has not shown sustainable consistency. Based on the results of the study, it can be concluded that the role of the village government in managing environmental cleanliness has been running quite well, but it still needs improvement, especially in the provision of facilities and infrastructure, equitable distribution of socialization activities, consistency of supervision, and the implementation of more effective strategies to foster public awareness.